2021
DOI: 10.1108/hcs-03-2021-0010
|View full text |Cite
|
Sign up to set email alerts
|

The promises and the reality of smart, digital telecare in England

Abstract: Purpose This paper asks how the introduction of “smart” digital technologies might affect the goals that can be attributed to telecare for older people, by those coordinating its provision. Design/methodology/approach A total of 29 in-depth, qualitative interviews were conducted with local authorities, housing associations and other organisations coordinating smart telecare provision, as well as telecare manufacturers and suppliers. Interviews were analysed by using qualitative thematic analysis. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
(76 reference statements)
1
3
0
1
Order By: Relevance
“…We then contrasted these frameworks to explore points of convergence and divergence in responses. As we explore below, the data indicated broad agreement across a number of areas related to the research questions, particularly among stakeholders from local authorities and the technology and care sectors (findings that echoed other studies of technology and care in England [45,60]). There were, however, some key areas of disagreement and tension, which we detail in the next section.…”
Section: Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…We then contrasted these frameworks to explore points of convergence and divergence in responses. As we explore below, the data indicated broad agreement across a number of areas related to the research questions, particularly among stakeholders from local authorities and the technology and care sectors (findings that echoed other studies of technology and care in England [45,60]). There were, however, some key areas of disagreement and tension, which we detail in the next section.…”
Section: Methodssupporting
confidence: 57%
“…However, there is a risk that underestimating the importance of wraparound services will waste resources, as some users will either abandon technologies or be unable to take full advantage of any benefits. As Stirling and Burgess [60] noted in a recent paper exploring smart digital TEC devices, "[t]he technology won't work on its own" (p. 52). If there is no provision of wraparound support, there is also a risk that unpaid carers will be burdened by additional tasks, as has been highlighted in research exploring telecare [69].…”
Section: Discussionmentioning
confidence: 99%
“…Just as recent research found unpaid carers are treated as ‘resources’ whose involvement is taken for granted when they provide the response for telecare services (ibid. ), paid responders too are underappreciated within the design of telecare services and products (Stirling & Burgess, 2020 ). Even as telecare services become increasingly predictive, highlighting issues before crisis is reached, technology alone cannot act on data generated by monitoring devices—a human response will instead be required before the moment of an emergency (ibid.).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, despite generalised inclusion recommendations in UK housing policy, at a local level it is not clear what typologies are needed for new housing developments for older people (Stirling and Burgess 2021). There is a lack of knowledge in relation to older people's experience of space both outside and inside their home, and a lack of clear process and principles towards designing inclusive buildings.…”
Section: Introductionmentioning
confidence: 99%